2019
DOI: 10.1111/joor.12819
|View full text |Cite
|
Sign up to set email alerts
|

Class II functional appliance treatment and dynamic three‐dimensional mimic muscle evaluation

Abstract: Background Functional appliances have skeletal and dentoalveolar treatment effects, but knowledge on their effect on facial expressions is limited. Objective To analyse changes in facial expressions, using three‐dimensional (3D) mimic muscle evaluation, in growing children with Class II malocclusion and large overjet, undergoing functional appliance treatment. Methods Fifteen growing children with Class II division 1 malocclusion, selected prospectively, had dynamic 3D recordings of facial expressions prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Therefore, it was speculated that the condylar movement symmetry increased after CFA treatment. These findings are consistent with the results obtained by Antonarakis and Kiliaridis[ 32 ], who revealed a trend toward greater symmetry after MA treatment compared with pre-treatment conditions. Previous occlusal studies revealed that the occlusal interference was reduced and that the occlusion became more balanced and stable in patients with class II malocclusion after orthodontic treatment[ 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it was speculated that the condylar movement symmetry increased after CFA treatment. These findings are consistent with the results obtained by Antonarakis and Kiliaridis[ 32 ], who revealed a trend toward greater symmetry after MA treatment compared with pre-treatment conditions. Previous occlusal studies revealed that the occlusal interference was reduced and that the occlusion became more balanced and stable in patients with class II malocclusion after orthodontic treatment[ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…And Blaschke et al [ 31 ] reported that these spatial variations might not be clinically meaningful. In contrast, the study by Antonarakis et al [ 32 ] on facial expressions revealed that adolescents with Class II Division 1 malocclusion exhibited greater asymmetry in mouth width during repose and while smiling than adolescents with Class I malocclusion. The facial expression and activity of the masticatory muscles in the cephalofacial region are related to neuromuscular control functions.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, ROM in lips and jaw was measured using the SmartEyeV R Pro-MME (Mimic Muscle Evaluation) (SmartEye AB, Gothenburg). MME is an add-on that tracks lip and jaw movements and has been shown to be a reliable instrument in earlier studies [41,[43][44][45]. The SmartEyeV R Pro system was originally a head and gaze tracking system that measure head pose and gaze direction in full 3D.…”
Section: D Motion Analysis Of Lips and Jawmentioning
confidence: 99%
“…( Rongo et al, 2019 , Perrotta et al, 2019 , Idris et al, 2019 ) Numerous myofunctional gadgets have been created since Newel first introduced the mouth screen in 1912, these include twin oral screens and oral shields. ( Tentolouri et al, 2021 , Antonarakis and Kiliaridis, 2019 , Brierly, 2017 ).…”
Section: Discussionmentioning
confidence: 99%